THE PERCEPTION OF SCHOOL DIRECTORS IN THE CITY OF JAGUARIÚNA ABOUT COMBAT SPORTS - Alba Iara Cae Rodrigues; Arlindo Antonio Baião Junior; Marcelo Moreira Antunes; José Julio Gavião de Almeida (Journal of Physical Education)
ABSTRACT The objective of this study was to understand the perceptions of elementary school leaders in the municipality of Jaguariúna (State of São Paulo, Brazil) about the benefits that combat sports can bring to education in Physical Education classes or as extracurricular activities and the possibilities to enabling this process. Semi-structured interviews were conducted with school directors and coordinators in all 15 public and private schools, totalling 30 interviews. Most of the interviewed had little contact with combat sports and only three had this activity at the school. The interviews were recorded, transcribed, and organized for qualitative textual analysis. The results point out that combat sports are valuable teaching tools in elementary schools, and that in order for their benefits to be achieved, they should be developed following school regular activities, and the professionals must be inserted in the school context. Several benefits were emphasized by the school leaders, including aspects of student attitudes, transmission of values, emotional development, social relations and benefits related to physical activity.